PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS EDMODO TERHADAP KEMAMPUAN PENALARAN MATEMATIS - Febby Ramdani; Ana Setiani; Hamidah Suryani Lukman (Jurnal PEKA (Pendidikan Matematika), 2021)
This study aims to determine the feasibility of Edmodo-based learning media for students' mathematical reasoning skills. Learning using Edmodo-based media has the advantage that it can be done anywhere and anytime so that it can help students become easier in mathematical reasoning. Analysis of mathematical reasoning ability is based on indicators (1) presenting mathematical statements orally, written, drawing, and diagram (2) performing mathematical manipulations (3) examining the validity of an argument and (4) determining the pattern or nature of mathematical symptoms to make generalizations.This research was conducted at SMP Uswatun Hasnah, Cisolok District, Sukabumi District. This research is development research with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation.). data collection used in this study is with several instruments namely expert sheets, student questionnaires and 4 questions of mathematical reasoning. The results of the research obtained the percentage of the ideal aspects of content/ material from media experts by 73.3% means that the criteria are feasible, expert material percentage of material aspects of 72.5% means that the criteria are feasible and the learning aspect of 69.1% means that the criteria are feasible, the average of the responses of 10 students is worth 35 which means that the criteria are practical, and the results of 4 questions of mathematical reasoning ability test given to get results that after use Edmodo-based learning media can improve the mathematical reasoning of students. The conclusion of this research is a learning media based on Edmodo towards the mathematical reasoning ability of students worthy to be applied.